Perencanaan Strategis SI/TI Pada BP3MI Sumatera Selatan Menggunakan Ward And Peppard - Tria Nanda Mughny; Dicky Pratama (PPPM Institut Teknologi Pagar Alam, 2025)
The utilization of Information Systems and Information Technology (IS/IT) is a strategic necessity for BP3MI South Sumatra to enhance the effectiveness of placement and protection services for Indonesian Migrant Workers (PMI). However, the integration of existing systems such as SIDABIT, TNDE, E-KIN, SPBW, and SISKO remains suboptimal, several processes are still performed manually, and no strategic IS/IT planning document is available as a foundation for long-term development. These conditions highlight the urgency for BP3MI to establish a structured strategic direction for IS/IT utilization that aligns with service needs. This study employs the Ward and Peppard methodology through Value Chain, PEST, SWOT, and Critical Success Factors analyses to identify the current organizational condition and formulate the required strategies. The study produces several key outputs, including a strategic IS/IT planning model consisting of Information System strategy, Information Technology strategy, and IS/IT management strategy, as well as a portfolio of prioritized applications such as SIDABIT Enhanced, Customer Relationship Management (CRM) for PMI, an IoT-based PMI Monitoring System, and an AI/Blockchain-based Document Verification System. It also provides an application contribution mapping using the McFarlan Strategic Grid and a five-year IS/IT development roadmap to guide phased implementation. The analysis further shows that BP3MI possesses strengths in service infrastructure and available central systems but still faces weaknesses such as limited system integration and human resource constraints, along with external threats including human trafficking, overcharging practices, regulatory changes, and data security risks. This study has limitations related to the dominance of qualitative data, restricted access to some technical information, and the absence of system testing, thereby requiring further research to validate implementation effectiveness.